Chinese Logistics Efficiency Analysis on the Basis of Different Regions - Wang, Xin (2012)
Logistics industry is treated as an essential part for economy development. In 2011, it is estimated that the GDP contribution of logistics industry is 14 trillion Yuan in China. This accounts for 17.7% of the total volume GDP of last year. However, low efficiency of Chinese logistics industry leads to high costs of the circulation commodity which was veiled to public last year. This low efficiency problem caused a hot discussion over the whole country last year. Currently, there are very few published papers which focus on the logistics development in China. Most of the existent ones merely list the efficiency calculation process without giving the detailed result explanations as well as relevant recommendations for problem solving.